2012
DOI: 10.1007/s12011-012-9580-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to [Cr3O(O2CCH2CH3)6(H2O)3]+ in Wistar Rats Fed Normal or High-Fat Diets Does Not Alter Glucose Metabolism

Abstract: The essentiality of chromium(III) has been the subject of much debate, particularly in healthy subjects. Chromium(III)-containing supplements are widely used for body mass loss, building of lean muscle mass, and improving glucose and lipid metabolism. [Cr3O(O2CCH2CH3)6(H2O)3]+, Cr3, is one of the most-studied chromium nutritional supplements. The current study evaluates the effects of long-term (15 months) supplementation with Cr3 on body mass and glucose metabolism in Wistar rats on traditional and cafeteria-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The Cr(III) treatment is helpful for glycaemic control in diabetic patients. On the other hand, the results obtained by Herring et al [ 54 ] suggest that long-term (15 months) Cr3 supplementation does not significantly impact metabolic responses in blood glucose concentration to glucose and insulin in male rats’ intake of a high-fat diet, high-carbohydrate cafeteria-style diet or normal diet. By contrast, Cr3 supplementation at doses of 10 and 50 mg kg −1 diet for 8 weeks increased the kidney Fe content in rats fed a high-fat diet [ 55 ].…”
Section: Discussionmentioning
confidence: 98%
“…The Cr(III) treatment is helpful for glycaemic control in diabetic patients. On the other hand, the results obtained by Herring et al [ 54 ] suggest that long-term (15 months) Cr3 supplementation does not significantly impact metabolic responses in blood glucose concentration to glucose and insulin in male rats’ intake of a high-fat diet, high-carbohydrate cafeteria-style diet or normal diet. By contrast, Cr3 supplementation at doses of 10 and 50 mg kg −1 diet for 8 weeks increased the kidney Fe content in rats fed a high-fat diet [ 55 ].…”
Section: Discussionmentioning
confidence: 98%
“…Some reports have shown that chromium(III) has beneficial effects for the organism with disturbances of glucose and lipid metabolism [ 4 , 17 , 31 ]. However, data from the experiments conducted in healthy individuals quite often explicitly show lack of any favourable impact of Cr(III) on carbohydrates/lipid metabolism [ 27 , 32 34 ]. Our study [ 27 ] showed no effect of Cr3 at doses 100–1000 mg of Cr(III)· kg −1 diet on serum glucose, total cholesterol, LDL-cholesterol, and HDL-cholesterol concentration (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy Sprague-Dawley rats treated daily with 20 μg· kg −1 body mass as Cr3 intravenously for 12 weeks had lower blood plasma insulin, total cholesterol, LDL, HDL and triglycerides but not glucose levels [ 31 ]. The data obtained by Herring et al [ 32 ] strongly suggest that long-term (15-month) Cr3 supplementation does not significantly affect metabolic responses in blood glucose concentration to glucose and insulin in male Wistar rats consuming a normal diet or high-fat, high-carbohydrate cafeteria-style diet. Also Król et al [ 33 ] confirmed that supplementary Cr3, given in the dosages 0.6 and 3 mg· kg −1 b.m.…”
Section: Discussionmentioning
confidence: 99%
“…This statement falls in agreement with the observations that supplementary Cr, no matter what chemical form or dosage is applied, has no effect on a healthy organism, both in animals and humans. Recently, Herring et al [ 48 ] studied the same Cr compound (Cr3 or CrProp) in healthy rats fed cafeteria-style diets (high-fat and high-carbohydrate diets) in a long exposure experiment. After a 15-month feeding of rats using those diets, CrProp at a dosage of 1 mg/kg b.m./day had no effect on body mass, organ masses (liver, kidneys, lungs, and heart), or visceral fat mass.…”
Section: Discussionmentioning
confidence: 99%